2013
DOI: 10.1155/2013/932863
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Profile of Xanthelasma Palpebrarum

Abstract: Xanthelasma palpebrarum (XP) are yellow plaques that occur most commonly near the inner canthus of the eyelid and are often associated with atherosclerosis, dyslipidemia, and coronary artery disease. This study was planned to address the issue of associated cardiovascular morbidity in xanthelasma patients attending our cardiac clinic. Materials and Methods. A total of 61 patients were detected to be having xanthelasma and constituted the study group. The control group constituted of 130 apparently normal indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 5 publications
(9 reference statements)
2
21
0
1
Order By: Relevance
“…In an earlier review, it was determined that half of the patients with xanthelasma had normal serum lipid levels and half manifested lipid dysregulation; there were no distinguishing microscopic findings between the two groups [20]. In another series, 7% of patients with xanthelasma had coronary artery disease [21]. Xanthelasma has been studied as a marker of premature atherosclerosis by discovering ultrasonographic thickening of the carotid intima [22].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier review, it was determined that half of the patients with xanthelasma had normal serum lipid levels and half manifested lipid dysregulation; there were no distinguishing microscopic findings between the two groups [20]. In another series, 7% of patients with xanthelasma had coronary artery disease [21]. Xanthelasma has been studied as a marker of premature atherosclerosis by discovering ultrasonographic thickening of the carotid intima [22].…”
Section: Discussionmentioning
confidence: 99%
“…a) or xanthoma tendinosum . It has been advised that all patients with XP should be investigated for serum lipid profile as well as for other major risk factors of coronary artery disease …”
Section: Xanthelasma Palpebrarummentioning
confidence: 99%
“…Several types of cutaneous xanthomas have been described. Xanthelasma palpebrarum (XP) is the well‐known type of xanthomas occurring as yellowish lesions on the eyelids, often causing a cosmetic problem . It may represent a localized idiopathic cutaneous phenomenon or may be a sign of systemic hyperlipidemia of varying degree .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XP most commonly occurs in the fourth and fifth decade of individual life. According to many previously conducted epidemiological studies, XP is highly associated with atherosclerosis, cardiovascular disease, diabetes, obesity and pancreatitis (Dey, Aggarwal, & Dwivedi, 2013;Pandhi et al, 2012). A number of previously conducted research also identified increased biochemical lipid profiles for patients with XP such as, higher level of LDL and VLDL cholesterol and lower level of HDL cholesterol which are established predictors of cardiovascular diseases (Kavoussi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%